2016
DOI: 10.1684/epd.2016.0882
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment strategies for epilepsy revisited: starting early or late? One drug or several drugs?

Abstract: There are two popular strategies for current drug treatment of epilepsy; starting early may be better and polytherapy conveys advantages over monotherapy. This review briefly examines if the historical record is much of a guide to determine the clinical value of these two strategies. Great clinical scientists of the 19th and early 20th century, such as Sir William Gowers, and William Aldren Turner, offered vivid single case studies and showed early results of seizure remission in groups of subjects. The histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…The broad spectrum activity of Phenobarbital against many types of seizure and its lower cost makes it to be used more frequently in our setting. 34 …”
Section: Discussionmentioning
confidence: 99%
“…The broad spectrum activity of Phenobarbital against many types of seizure and its lower cost makes it to be used more frequently in our setting. 34 …”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, physicians suggested that the second AED should be considered when the first AED failed for lack of efficacy . However, the results of studies comparing combination therapy and alternative therapy have not provided evidence for which therapy should be chosen . Our study provided direct evidence that combination therapy offered larger probability of seizure freedom for patients with first AED failure due to lack of efficacy.…”
Section: Discussionmentioning
confidence: 61%
“…When the first drug fails, there are three options to control seizures: alternative therapy, combination therapy, or increase dosage of the first AED . Previous studies included patients with failure of the first AED due to insufficient efficacy or side effects, but the results have not demonstrated which therapy is better . Patients switching to a different AED because of side effects have a higher probability of seizure freedom on alternative therapy, which may bias the results …”
Section: Introductionmentioning
confidence: 99%
“…14,17,19 QoL was not significantly related to the number of different ATC categories a participant had been prescribed medications from. Given that there is limited evidence for the effectiveness in seizure control whether AED monotherapy or polytherapy is used 13 and that AED polytherapy may be associated with a lower QoL, there seems little compelling need to use AED polytherapy in the management of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, no compelling evidence exists for differences in seizure outcome whether monotherapy or polytherapy was used. 13 A recent study has shown that people with epilepsy who received AED monotherapy compared with polypharmacy experienced fewer ongoing seizures and reported a better quality of life (QoL) (when adjusting for seizure status). 14 This was supported by a recent US study that showed AED polypharmacy was associated with a worse QoL, even when adjusting for severity of epilepsy.…”
Section: Aeds Monotherapy and Polypharmacymentioning
confidence: 99%